The Influence of Village Apparatus Competence, Clarity of Budget Targets, Internal Control System and Siskeudes on Village Fund Management Accountability - Permadi Suryawan, Bayu; Paranoan, Selmita; Yamin, Nina Yusnita; Iqbal, Muhammad (Lafadz Jaya Publisher, 2025)
The large amount of village funds that go to the village government makes it prone to misuse. Therefore, the community demands good accountability in managing village funds. The aim of this research is to determine the influence of the competence of village officials, clarity of budget targets, internal control systems and siskeudes on accountability in managing village funds. The research was carried out in all villages in the Pamona brother’s region, Poso Regency. The method used in this research is a quantitative method with primary data obtained from 110 respondents who filled in the questionnaire. The results obtained in the research show that the competence of village officials and clarity of budget targets do not affect the accountability of village fund management. Meanwhile, the internal control system and siskeudes variables influence the accountability of village fund management.